2021
DOI: 10.1002/jbt.22789
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin–angiotensin system in the development of cataract formation in angiotensin‐II‐induced experimental rats

Abstract: Previously, we established several facts regarding hypertension-associated cataractogenesis. As a follow-on study, we evaluated the role of the renin-angiotensin system (RAS) in angiotensin-II (Ang-II)-induced cataract formation in experimental hypertensive rats. Sprague-Dawley male albino rats (150-180 g) were used for the present experiment. The animals were divided into four groups, with six animals in each group. During the 12 weeks of the experimental protocol, the normal group received sterile water (1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These terms have a close relationship to visual function, which suggested that the visual function might be impaired due to Ang II. In fact, RAS plays an important role in visual function from various aspects [30][31][32] . Researchers have found that RAS could promote age-related macular degeneration in mouse models and angiotensin II type 1 receptor (AT1R) blocker could reversed the retinal pigmented epithelial cell condition and visual function [30] .…”
Section: Angiotensin II and Retinal Arterymentioning
confidence: 99%
“…These terms have a close relationship to visual function, which suggested that the visual function might be impaired due to Ang II. In fact, RAS plays an important role in visual function from various aspects [30][31][32] . Researchers have found that RAS could promote age-related macular degeneration in mouse models and angiotensin II type 1 receptor (AT1R) blocker could reversed the retinal pigmented epithelial cell condition and visual function [30] .…”
Section: Angiotensin II and Retinal Arterymentioning
confidence: 99%
“…Additionally, the renin-angiotensin system (RAS) is present in human aqueous humor [15]. The local RAS, operating through this aqueous humor circulation, is involved in cataract formation in angiotensin II-induced rats [16], and ARBs are effective in suppressing oxidative stress in diabetic cataracts [17]. Therefore, the RAS is hypothesized to participate in oxidative stress associated with the formation of diabetic cataracts.…”
Section: Introductionmentioning
confidence: 99%